Analisis Kebijakan Penguatan Pendidikan Karakter Bela Negara Di SMK Sore Tulungagung - Khusnaini Khusnaini; Budiono Budiono (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: The Strengthening of National Defense Character Education Policy that has been implemented at the Vocational High School Sore Tulungagung in 2014/2015 is a new character education development policy. The policy must be analyzed to give other schools a clear picture of the effectiveness of character education. Therefore the researcher intends, to find out the implementation suitability and evaluate the effectiveness of the policy of strengthening the character education of the National Defense Vocational High School Sore Tulungagung. Through qualitative research methods, by triangulating research data, researchers analyze data by studying theory through the reduction of interview results. The results obtained, the planning of strengthening the character education of National Defense is not good, because of the lack of reference laws that are used, indicators of achievement of the basic values of the character of defending the country. In the implementation of the policy declared quite good, seen activities that teach nationality insight to students, but there needs to be supervision from the implementation team. Finally, the evaluation stage of the policy is still not good, because the evaluation of character education is in the form of violations in general, not on indicators of the basic values of Defending the State.Keywords: Policy, Character Education, National Defense Abstrak: Kebijakan Penguatan Pendidikan Karakter Bela Negarayang telah dilaksanakan di SMK Sore Tulungagung tahun 2014/2015 merupakan kebijakan pengembangan pendidikan karakter baru. Kebijakan tersebut harus dianalisis agar memberi gambaran jelas kepada sekolah lain efektifitas pendidikan karakter tersebut. Maka dari itu penelitian ini bermaksuduntuk mengetahui implementasi dan mengevaluasi efektifitas kebijakan penguatan pendidikan karakter Bela Negaradi SMK Sore Tulungagung. Melalui metode penelitian kualitatif, dengan triangulasi data-data penelitian, peneliti menganalisis data dengan kajian teori melalui reduksi hasil wawancara. Hasil penelitian yang didapatkan, perencanaan penguatan pendidikan karakter Bela Negarakurang baik, sebab minimnya acuan perundangan yang dipakai, indikator ketercapaian nilai-nilai dasar karakter bela negara. Pada implementasi kebijakan dinyatakan cukup baik, terlihat adanya kegiatan-kegiatan yang mengajarkan wawasan kebangsaan pada peserta didik, namun perlu adanya pengawasan dari tim pelaksana. Terakhir, tahap evaluasi kebijakan masih kurang baik, sebab evaluasi pendidikan karakter ini berupa pelanggaran secara umum, bukan pada indikator nilai-nilai dasar Bela Negara.Kata kunci: Kebijakan, Pendidikan Karakter, Bela Negara